Closing the gap between training needs and training provision in addiction medicine. (May 2020) - Arya, Sidharth; Delic, Mirjana; Ruiz, Blanca Iciar Indave; Klimas, Jan; Papanti, Duccio; Stepanov, Anton; Cock, Victoria; Krupchanka, Dzmitry
Abstract : Substance use disorders pose a significant global social and economic burden. Although effective interventions exist, treatment coverage remains limited. The lack of an adequately trained workforce is one of the prominent reasons. Recent initiatives have been taken worldwide to improve training, but further efforts are required to build curricula that are internationally applicable. We believe that the training needs of professionals in the area have not yet been explored in sufficient detail. We propose that a peer-led survey to assess those needs, using a standardised structured tool, would help to overcome this deficiency. The findings from such a survey could be used to develop a core set of competencies which is sufficiently flexible in its implementation to address the specific needs of the wide range of professionals working in addiction medicine worldwide.